2019
DOI: 10.1016/j.heliyon.2019.e02918
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of benzene air quality standards, monitoring methods and concentrations in indoor and outdoor environment

Abstract: Benzene is a proven carcinogen. Its synergistic action with other pollutants can damage different components of the biosphere. Literature comparing the air quality standards of benzene, its monitoring methods and global concentrations are sparse. This study compiles the worldwide available air quality standards for benzene and highlights the importance of strict and uniform standards all over the world. It was found that out of the 193 United Nation member states, only 53 countries, including the European Unio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 131 publications
(148 reference statements)
1
61
0
1
Order By: Relevance
“…Noteworthy, at the European Community level, the resolution of 13 March 2019, defends clean air for everyone and highlights that people spend almost 90% of their time in indoors [6]. In these environments, the air can be significantly more polluted compared to outside [7] and, therefore, considered mandatory to issue indoor air quality certificates for both new and old buildings. From this perspective, it urges member states to adopt and implement measures to combat air pollution at the source.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, at the European Community level, the resolution of 13 March 2019, defends clean air for everyone and highlights that people spend almost 90% of their time in indoors [6]. In these environments, the air can be significantly more polluted compared to outside [7] and, therefore, considered mandatory to issue indoor air quality certificates for both new and old buildings. From this perspective, it urges member states to adopt and implement measures to combat air pollution at the source.…”
Section: Introductionmentioning
confidence: 99%
“…However, each different area shows different noise level since there are various factors both from industrial activities and other human activities. Several studies in scientific publications on air quality have been reported [19][20][21]. Where the results show that the average benzene level in ambient air in Asian countries (371μg/m 3 ) was about 3.5 times higher than the level of benzene in the room (111μg/m 3 ).…”
Section: Resultsmentioning
confidence: 97%
“…These compounds are emitted as combustion byproducts of fossil fuels and biomass, including motor vehicles and wildfires, and through volatilization from crude oil or its derivatives, including gasoline and industrial solvents [ 4 , 5 , 6 , 7 ]. BTEX compounds are classified as hazardous air pollutants (HAPs) and are regulated by a large number of agencies worldwide including the United States Environmental Protection Agency (US EPA) and the California Air Resources Board (CARB) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%